Molecular mechanisms of tumor resistance to radiotherapy - Wu, Yu; Song, Yingqiu; Wang, Runze; Wang, Tianlu (Molecular cancer, 2023)
Cancer is the most prevalent cause of death globally, and radiotherapy is considered the standard of care for most solid tumors, including lung, breast, esophageal, and colorectal cancers and glioblastoma. Resistance to radiation can lead to local treatment failure and even cancer recurrence. In this review, we have extensively discussed several crucial aspects that cause resistance of cancer to radiation therapy, including radiation-induced DNA damage repair, cell cycle arrest, apoptosis escape, abundance of cancer stem cells, modification of cancer cells and their microenvironment, presence of exosomal and non-coding RNA, metabolic reprogramming, and ferroptosis. We aim to focus on the molecular mechanisms of cancer radiotherapy resistance in relation to these aspects and to discuss possible targets to improve treatment outcomes. Studying the molecular mechanisms responsible for radiotherapy resistance and its interactions with the tumor environment will help improve cancer responses to radiotherapy. Our review provides a foundation to identify and overcome the obstacles to effective radiotherapy.